Designing Writing Assessment Tasks for Junior High School - Nur Aisyah Zulkifli (Indonesian Journal of Integrated English Language Teaching, 2016)
Junior High School is the next step for students in learning English. In elementary school, learning target that should be reached by student is vocabulary mastery, then introduced by four language skills-speaking, reading, listening, and writing- in Junior High School. It can’t be denied, even they have Junior High School, and it is still found students who are difficult to write sentences in English. In fact, when English Education Department (EED) students are asked ‘how to asses students writing for Junior High School?’ They answered by writing paragraph. And, how to give students score? They answered by using rubric like stated at ‘Language assessment book by Arthur Huges’. Actually, writing assessment is not only focused on writing paragraph. For Junior high school, there are some writing performance can be used to assess students writing, and to give score it should be appropriate with the level of the student. The rubric used by EED students is the rubric for English as a second language. Therefore in this paper, writer describes how to design writing assessment task for Junior High School and its rubric. Hopefully, this paper can help EED students in designing writing assessment task when they do teaching practice (PPL) and making instrument for their research.